Chloroform Extract of Plumbago zeylanica Linn. Roots Ameliorates the Epidermal Thickness of Imiquimod-induced Psoriatic Mice through Cell Cycle and Apoptosis - Purwoko, Mitayani; Indarto, Dono; Kariosentono, Harijono; Purwanto, Bambang; Soetrisno, Soetrisno; Cilmiaty, Risya (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Psoriasis vulgaris is a chronic skin disease which is characterized by recurrent scales on skin. The global prevalence of this disease has increased in ten years. Plumbagin is an active compound in the P. zeylanica Linn. Some recent studies revealed that P. zeylanica Linn extracts have the antiproliferative activity, which is used for treatment of some human diseases. The aim of this study was to investigated the effect of Chloroform extract of P. zeylanica Linn roots (CEP) on epidermal thickness of Imiquimod-induced psoriatic mice. Methods: This was a post-test only control group design. A total of 42 male BALB/c mice was divided into six groups. Mice in treatment groups orally received 25, 50, and 100 mg/kg body weight CEP, respectively while positive control orally received 1 mg/kg body weight Methotrexate for seven days. Evaluation of epidermal thickness based on histological changes, serum IL-23 level by ELISA, and Cyclin-dependent kinase 2, Cyclin A, and Caspase-3 expressions by immunohistochemistry. Results: Administrations of CEP decreased the epidermal thickness of psoriatic plaques in all treatment groups (p = 0.002, 0.003, and 0.016 respectively) compared to negative control but it did not reduce the serum IL-23 level. The expressions of CDK2 and Cyclin A reduced in T2 and T3 groups and the expression of Caspase-3 increased was only in T3 group. Conclusion: Chloroform extract of P. zeylanica Linn roots administrations reduce the epidermal thickness of Imiquimod-induced psoriatic mice by inhibition of keratinocyte cell cycle and induction of Caspase-3 expression.